(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: This study aimed to evaluate the acute of the mouthwash containing chlorhexidine and chlorine dioxide in mice. Subject and method: Healthy Swiss albino white mice were randomized into test and physiological groups (n=10). The test solution (0,1% CHX, 0,5% ClO2) was orally administered to the test groups and the distilled warter was given to the normal group. The mortality, changes in body weight, and clinical signs were monitored 14 days after treatment with the tested mouthwash. Results: Any mortalities or changes in body weight in mice were found. Within 30 minutes after being given the test material, 30% of mice displayed watery, red eyes and difficulties fully opening them but returned to normal afterward. Conclusion: The combination of ,1% CHX, 0,5% ClO2 does not cause any mortality in mice after a single dose for 14 days.